Improving studentsâ metacognitive awareness through implementing learning journal - Nurajizah, Ulfa; Windyariani, Sistiana; Setiono, Setiono (University of Muhammadiyah Malang, 2018)
The process of learning and understanding of science has relevance to the level of metacognitive awareness. The purpose of this study was to find out whether the use of learning journals have an effect on students metacognitive awareness. This study was quasi-experimental research with non-equivalent pretest-posttest control group design. The subjects of this study were second semester of VII grade students of State Junior High School 5 of Sukabumi in 2017-2018 academic year. Metacoginitive awareness was measured by using Metacognitive Awareness Inventory (MAI). The data obtained from pretest and posttest were calculated into N-gain score. These data were analyzed by using independent t-test. The results showed that N-gain score for metacognitive awareness in experimental and control class were 0.70 and 0.22 in sequence. Meanwhile, the t-test results indicated that there was a significant difference between learning by using learning journals and without using learning journal in increasing students metacognitive awareness. It showed that students metacognitive awareness in the experimental class were better than the control class. It can be suggested that implementing learning journal is potential media in improving studentsâ metacognitive awareness.